Urgensi Pengadopsian Ekosida Dalam Sistem Hukum Nasional Sebagai Respon Menghadapi Ancaman Krisis Lingkungan Hidup - Jesica Lestari; Alfarizi Dwiki Hartanto; Dimas Aditya Ashari; Maheswari Kinanthi Prabowo Putri; Revina Agit Olivia (Amal Insani Foundation, 2024)
The right to a healthy environment is enshrined in Article 28H paragraph (1) and Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia. These provisions assert the entitlement of every individual to a favorable living environment grounded in environmental understanding. Nonetheless, this principle stands in stark contrast to the prevailing reality. Within WALHI's documented records, three instances of ecocide crimes have occurred in Indonesia, encompassing the Lapindo mudflow, forest and peatland fires in Central Kalimantan, and the development of hydropower plants in Koto Panjang. Ecocide serves as a glaring testament to the classification of environmental offenses as extraordinary crimes, given their capacity to erode the fundamental tranquility of human existence. This composition adopts a normative juridical approach, employing legislative, comparative, conceptual, and analytical dimensions. The focal aim of this discourse is to scrutinize the ecocide threat, its incorporation within a framework of conscientiousness, and its correlation with Pancasila as a responsive measure against environmental perils. Recommendations set forth encompass: a) the formulation of definitive legislation in Indonesia concerning ecocide; and b) a comprehensive legal examination, entailing an in-depth analysis of the scope, regulatory orientation, and content, taking into profound account philosophical, sociological, and juridical facets.